2016
DOI: 10.5812/numonthly.35497
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Management of Lower Urinary Tract Symptoms Related to Benign Prostatic Obstruction in a Contemporary Series of Renal Transplant Recipients

Abstract: BackgroundThe kidney is the most frequently transplanted human organ worldwide. In patients with end-stage renal failure, renal transplantation improves both quality of life and life expectancy. The current literature indicates that the numbers of renal recipients over 60 years of age has increased in recent years.ObjectivesTo evaluate the prevalence and management of lower urinary tract symptoms (LUTS) related to benign prostatic obstruction (BPO) in a contemporary series of male renal transplant (RTx) recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A retrospective cohort study on 23.622 recipients [14] reported an incidence of 9.7% and 7.3% of BPH and TURP, respectively, 3 years after RT, without stratifying by age. More recently, a retrospective study on 131 recipients, showed a benign prostatic obstruction prevalence of 58% between 60 and 70 years, and 71% above 70 years [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort study on 23.622 recipients [14] reported an incidence of 9.7% and 7.3% of BPH and TURP, respectively, 3 years after RT, without stratifying by age. More recently, a retrospective study on 131 recipients, showed a benign prostatic obstruction prevalence of 58% between 60 and 70 years, and 71% above 70 years [15].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with an indwelling bladder catheter, we considered the sCr and eGFR levels before the catheterization. LUTS were categorized into mild (IPSS score 1-7), moderate (IPSS score [8][9][10][11][12][13][14][15][16][17][18][19], and severe (IPSS score [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. We considered the following UD variables: bladder capacity (< 100, 100-300, > 300 mL), Qmax (mL/s), detrusor pressure at Qmax (PdetQmax; cmH2O), PVR (< 1/3 of bladder capacity, > 1/3 of bladder capacity).…”
Section: Covariatesmentioning
confidence: 99%
“…Optimal bladder function is another important requirement. [8] After RT, urine flow increases, and preexisting BPH or BOO may cause urinary retention. [9] Urinary retention is the most predominant symptom of BOO.…”
Section: Discussionmentioning
confidence: 99%